2014
DOI: 10.1093/schbul/sbu104
|View full text |Cite
|
Sign up to set email alerts
|

Jumping to Conclusions, Neuropsychological Functioning, and Delusional Beliefs in First Episode Psychosis

Abstract: JTC is present in FEP. The specific association of JTC with clinical delusions supports a state, maintaining role for the bias. The associations of JTC with neuropsychological functioning indicate a separable, trait aspect to the bias, which may confer vulnerability to psychosis. The work has potential to inform emerging interventions targeting reasoning biases in early psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 61 publications
(95 reference statements)
8
63
0
2
Order By: Relevance
“…Lower IQ was also found associated with JTC in First Episode Psychosis 27,28 . Nonetheless, other studies on early psychosis did not detect any association with cognition, possibly due to small sample size 29,30 .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Lower IQ was also found associated with JTC in First Episode Psychosis 27,28 . Nonetheless, other studies on early psychosis did not detect any association with cognition, possibly due to small sample size 29,30 .…”
Section: Introductionmentioning
confidence: 80%
“…Another possible explanation lies in the fact that JTC seems to be more associated with the continuous distribution of delusions rather than with schizophrenia per se [11][12][13][14][15] . In fact, in a large casecontrol study on FEP patients carried out by Falcone 28 , adjusting for IQ and working memory abolished the relation between JTC and clinical status, but the association between JTC and delusion severity remained. Perhaps building a PRS based on the positive symptom dimension or delusions would be more associated with the bias.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Much of this work is narrowly balanced on a single task (the beads task), performance on which correlates strongly with working memory (another RDoC construct) and IQ. 19 Differences between psychotic patients and controls on the task are sizeable, Cohen's d = 0.61, 18 but modest compared to d ≈ 1.00 for many other neuropsychological main effects. Risen's context for thinking about how failures in any of several cold cognitive processes might allow for the formation and maintenance of abnormal beliefs may profitably be applied to expanding our thinking about the cognitive neuroscience constructs relevant to delusions.…”
mentioning
confidence: 96%
“…Many subsequent studies have confirmed this finding (for a review see Garety & Freeman, 2013). However, in much the same way as with theory of mind impairment, these studies have struggled to demonstrate an association with presence or severity of delusions (Dudley et al, 2011; Falcone et al, 2015; Freeman et al, 2014; Garety et al, 2013; Langdon, Ward, & Coltheart, 2010; Lincoln, Ziegler, Mehl, & Rief, 2010; Menon, Pomarol-Clotet, McKenna, & McCarthy, 2006; Moritz & Woodward, 2005; Mortimer et al, 1996; Ochoa et al, 2014; Peters, Thornton, Siksou, Linney, & MacCabe, 2008; So et al, 2012). …”
Section: Theories Of Delusionsmentioning
confidence: 99%